Undertreatment of human immunodeficiency virus in psychiatric inpatients: a cross-sectional study of seroprevalence and associated factors - Gonzalez-Torres MA (Dove Medical Press, 2015)
Miguel Angel Gonzalez-Torres,1,2 Miguel Angel Salazar,3 Manuel Imaz,4 Lucía Inchausti,1,2 Berta Ibañez,5 Aranzazu Fernandez-Rivas,1,2 Javier Pastor,3 Bosco Anguiano,3 Pedro Muñoz,3 Eduardo Ruiz,1,2 Rodrigo Oraa,3 Sonia Bustamante,1,2 Sofia Alvarez de Eulate,2 Ramón Cisterna4,61Department of Neuroscience, University of the Basque Country, 2Psychiatry Service, Basurto University Hospital, Bilbao, 3Mental Health Network of Biscay, Basque Health Service, Biscay, 4Microbiology Service, Basurto University Hospital, Bilbao, 5Navarra Biomed-Miguel Servet Foundation, Red de Investigación en Servicios Sanitarios y Enfermedades Crónicas (REDISSEC), Pamplona, 6Department of Microbiology, University of the Basque Country, Bilbao, SpainBackground: The aims of this study were to evaluate the prevalence of HIV and its associated demographic and clinical factors among psychiatric inpatients of a general hospital.Methods: This was a single-center, observational, cross-sectional study that included patients consecutively admitted to our unit aged 16 years or older and with no relevant cognitive problems. The patients were evaluated using a semistructured interview and an appropriate test for HIV infection.Results: Of the 637 patients who were screened, 546 (86%) who consented to participate were included in the analyses. Twenty-five (4.6%, 95% confidence interval [CI] 3.0–6.8) patients were HIV-positive. The prevalence was higher among patients with substance misuse (17.4%, 95% CI 9.7–28.8). All except one of the 25 patients knew of their seropositive condition prior to participation in the study. Only 14 (56%) of the 25 seropositive patients had previously received pharmacological treatment for their infection. According to the multiple logistic regression analysis, the likelihood of HIV infection was lower in patients with higher levels of education and higher among patients who were single, had history of intravenous drug use, and had an HIV-positive partner, particularly if they did not use condoms. Among the patients with HIV infection, 18 (72%) had a history of suicide attempts compared with 181 (34.7%) of the patients without HIV infection (relative risk 2.1, 95% CI 1.6–2.7; P<0.001).Conclusion: HIV infection is highly prevalent in patients admitted to a psychiatric unit, especially those with a diagnosis of substance misuse. Seropositive patients show very poor treatment adherence. The risk of suicide seems to be very high in this population. Implementing interventions to reduce the suicide risk and improve adherence to antiretroviral therapy and psychotropic medications seems crucial.Keywords: severe mental illness, human immunodeficiency virus, adherence, epidemiology